Does SLNB substitute END in the future with the sole advantage of preventing shoulder morbidity?. (December 2021) - Bylapudi, BhanuPrakash; Rao, Vishal U.S.; Subash, Anand; Thakur, Shalini
Abstract: SLNB has emerged as a rational proposition in the management of early-stage oral cancer and has mixed responses within the oncological community. It is high time for the clinicians to look into the fact that, when a patient post-surgery has a regional recurrence within 6 months, it could be reasonable to believe that a tumor seed which was earlier an isolated tumor cell (ITC) or in the form of a micro-metastasis (MM) would have led to this. SLNB has the potential to become a standard of care in the future owing to the development and utility of better evaluation tools to pick nodal metastasis. It is not an overemphasizing statement to say that SLNB could become a standard recommendation in the near future, however, it still looks like a distant dream considering its logistical and technological limitations.